2015
DOI: 10.5430/wje.v5n3p73
|View full text |Cite
|
Sign up to set email alerts
|

Sex Education and Teenage Pregnancy in the Niger Delta: Implications for Secondary School Biology Curriculum in Nigeria

Abstract: Previous studies show that when Nigerian adolescent girls, especially those in the Niger Delta, become pregnant they drop out of school and may never go back again but become low level labourers or miscreants to the society. This study investigated the extent of teenagers involvement in sex, pre-disposition of females to pregnancy in the Niger Delta of Nigeria, the level of readiness of parents to help their teenage daughters if they become pregnant, the level of sex education in secondary schools, the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
5
1
Order By: Relevance
“…The findings contradict prior research, which found a low degree of self-efficacy among teachers when discussing the sexual health education component of the teaching process (Peskin et al, 2015;Rohleder, 2010). However, the findings are consistent with prior Malaysian studies that have emphasized that a teacher's knowledge of sexual health education will impact the success of the teaching process for youth with special needs (Salami, 2017). Furthermore, the findings indicate that the level of perception among the majority of the special education teacher in the Melaka Tengah district is moderate.…”
Section: Factors Studiedcontrasting
confidence: 52%
“…The findings contradict prior research, which found a low degree of self-efficacy among teachers when discussing the sexual health education component of the teaching process (Peskin et al, 2015;Rohleder, 2010). However, the findings are consistent with prior Malaysian studies that have emphasized that a teacher's knowledge of sexual health education will impact the success of the teaching process for youth with special needs (Salami, 2017). Furthermore, the findings indicate that the level of perception among the majority of the special education teacher in the Melaka Tengah district is moderate.…”
Section: Factors Studiedcontrasting
confidence: 52%
“…Moreover, information on prevention of STIs and contraception is rarely communicated to adolescents in Nigeria as a result of societal norms contradicting sexual and reproductive education to children and adolescents (Salami, 2015). There is a misconstrued widespread view that discussion of such topics with adolescents will provoke premarital activities (Eko et al, 2013), which is similar to what is practiced in Saudi Arabia (Farih, Khan, Freeth, & Meads, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bangladesh and Nigeria have similar religious values when considering reproductive health communication to adolescents. Certain aspects of reproductive health such as contraception and pubertal changes in adolescents are considered inappropriate to be communicated to adolescents (Alim et al, 2012; Eko et al, 2013; Salami, 2015).…”
mentioning
confidence: 99%
“…Teenage pregnancy remains a persistent global crisis that profoundly impacts the socioeconomic wellbeing of nations, citizens and families since it contributes to high dropout rates, lower academic achievements, early marriages and decreased school attendance for female learners (Molisiwa & Moswela, 2012). Additionally, teenage pregnancy among schooling girls may lead to sexually transmitted diseases, abortion, increased mortality rates as well as effecting the school enrollment (Amadi, 2019). These undesirable impacts have forced nations of the world to adopt different policy initiatives and intervention measures to curb the vice and the prevailing consequences.…”
Section: Introductionmentioning
confidence: 99%